STUDENTS’ DİFFİCULTİES İN THE FİELD OF CHEMİCAL KİNETİCS İN SECONDARY SCHOOLS AND METHODOLOGİCAL PRİNCİPLES OF THEİR ELİMİNATİON. - Nuriyeva , M. (EurasianUnionScientists, 2021)
In the article the main purpose is the development of new teaching methods that meet the learning difficulties in the field of chemical kinetics, which has been considered the most pressing problem in the teaching process of chemistry in secondary schools during recent years. Thus, in the article, in the direction of overcoming these difficulties in secondary schools, research-based criteria have been highlighted for selecting new pedagogical experiments by researching new methodological principles intended to be used in the teaching prosess of topics related to chemical kinetics with the application of modern training technologies and also the scheme reflecting the modeling methodology of the teaching process of chemical kinetics.